From elections to democracy : building accountable government in Hungary and Poland - Rose-Ackerman, Susan (Cambridge, UK ; New York : Cambridge University Press, 2005)
This study documents the weaknesses of public oversight and participation in policymaking in Hungary and Poland. It discusses five alternative routes to accountability including European Union oversight, constitutional institutions such as presidents and courts, devolution to lower-level governments, the use of neo-corporatist bodies, and open-ended participation rights.
Policymaking accountability and democratic consolidation -- Alternative routes to policy-making accountability -- Legacy of the past -- External accountability and the European Union -- Oversight -- Decentralized political accountability -- Public participation in policymaking: government procedures -- Civil society groups: overview -- Environmental advocacy organizations in Hungary -- Student and youth organizations in Poland -- Democratic consolidation and policy-making accountability.
Includes bibliographical references (pages 251-267) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Political participation -- Hungary; Transparency (Ethics) in government -- Hungary; Democracy -- Hungary; Political participation -- Poland; Transparency (Ethics) in government -- Poland; Democracy -- Poland; Participation politique -- Hongrie; Transparence (Sciences sociales) -- Hongrie; Démocratie -- Hongrie; Participation politique -- Pologne; Transparence (Sciences sociales) -- Pologne; Démocratie -- Pologne; POLITICAL SCIENCE -- Political Process -- General; Démocratie.; Elaboration d'une politique; Institutions politiques; Participation politique; Transparence; Hongrie; Pologne; Democracy; Political participation; Transparency in government; Hungary; Poland; Demokratie; Demokratisierung; Politische Beteiligung; Politischer Wandel; Polen; Ungarn; Democratisering; Verantwoordingsplicht; Politieke participatie; Beleidsvorming; Democratie